Impact of gestational low protein diet and postnatal bisphenol A exposure on chemically induced mammary carcinogenesis in female offspring rats - Varuzza, Muriele B. [UNESP]; Zapaterini, Joyce R. [UNESP]; Colombelli, Ketlin T. [UNESP]; Barquilha, Caroline N. [UNESP]; Justulin, Luis A. [UNESP]; Muñoz-de-Toro, Monica; Kass, Laura; Barbisan, Luis F. [UNESP] (Wiley, 2019)
This study evaluated the effect of gestational low protein diet (LPD) and/or postnatal bisphenol A (BPA) exposure on mammary gland development and carcinogenesis in female offspring. Pregnant Sprague-Dawley rats were fed a normal protein diet (NPD, 17% protein) or LPD (6% protein). At weaning, female offspring were distributed in four groups (NPD, LPD, NPD + BPA, and LPD + BPA) and received vehicle or BPA in drinking water (0.1%), during postnatal day (PND) 21 to 51. On PND 51, some female offspring were euthanized or received a single dose of 7,12-dimethylbenzoanthracene (DMBA, 30 mg/kg, i.g.) and were euthanized on PND 250. On PND 51, neither gestational LPD nor postnatal BPA exposure, individually or in combination, significantly altered the development of mammary gland tree, mean number of terminal structures or estrogen receptor beta (ER-β), proliferating cell nuclear antigen (PCNA) or caspase-3 protein expression in the mammary tissue. A significant reduction in mammary epithelial area (%) was observed in both LPD groups and a significant increase in ER-α protein expression was detected only in LPD group. In LPD + BPA group was observed a significant increase in both fat pad area (%) and in mean number of mammary epithelial cells positive for progesterone receptor (PR). On PND 250, the groups that received BPA presented lower latency and higher tumor incidence and tumor multiplicity and LPD + BPA group more aggressive tumors. These findings suggest that postnatal BPA exposure associated with gestational LPD is able to induce morphological changes in the mammary gland and increase susceptibility to mammary carcinogenesis.
Keywords: chemically induced mammary carcinogenesis; gestational low protein; mammary gland development; postnatal bisphenol A exposure